Aquifer Potential Analysis Based On Hydrostratigraphy and Geological Lineament In Kokap Region, Kulon Progo, Yogyakarta, Indonesia - R.A.T. - Listyani; Ignatius Adi Prabowo; Armindo Antonio De Jesus (CV FOUNDAE, 2023)
As a water-poor region, a study on the potential of water resources is urgently needed in the Kokap area, Kulon Progo. The purpose of this research is to carry out a hydrogeological survey to obtain an overview of water resources that can be approached from the groundwater aquifer potential. The method used is a hydrogeological survey in the field to determine the condition of morphology, rocks, geological structures, and hydrogeology; equipped with hydrostratigraphic analysis and geological lineament. The hydrostratigraphic analysis was made based on the interpretation of secondary data in the form of geoelectric, while the geological structure analysis was carried out based on the interpretation of DEM and Landsat imagery. The results showed that the Kokap area has hydrostratigraphy in the form of free aquifers 0 – 20 m thick and aquitards 0 – 8 m thick. Aquifug is at a depth of 4 - >20 m. With a lineament density of up to 808/km and supported by relatively intensive weathering, the Kokap area has the potential to have a fairly good groundwater aquifer configuration, with aquifer boundary types namely H1, H2, H4, H5 and V1, V2, V3.